Structured Training to the Patients of Chronic Obstructive Pulmonary Disease Reduces Frequency of Hospital Readmission (Delta Medical College Journal, 2018)
Background: Patient education after treatment of acute exacerbation in patients with chronic obstructive pulmonary disease (COPD) prevents frequent hospital readmission and improve quality of life.Objectives: To observe the impact of providing structured training to patients of COPD on repeated hospital admission.Materials and method: This prospective comparative study was carried out in the inpatient department of Medicine and Pulmonology Unit, Sir Salimullah Medical College and Mitford Hospital, Dhaka, Bangladesh, from January 2010 to June 2011. A total of 144 admitted patients with COPD with an attack of acute exacerbation were included in this study without having any significant or chronic comorbidity. Of the 144 patients, 72 were randomly allocated for receiving structured training (cases; Group-A) and the rest 72 patients did not receive the training (controls; Group-B).Results: The pertinent demographic characteristics, smoking status, and knowledge about different aspects of COPD, and medications used during acute exacerbation of COPD before intervention were almost similar between the groups. Over 30% of the patients who received structured training needed no hospital admission, 58.3% needed only one and 11.1% needed 2 or more admissions, while the other group required two or more admissions during the same period (p < 0.001). The duration of hospital stay was significantly less in case group. Number of > 2 consultations with physicians was significantly higher in the former group (26.4% vs. 6.9%) (p = 0.002), indicating an increased awareness on the part of that group.Conclusion: Structured training to COPD patients significantly reduced hospitalization and hospital stay for an acute exacerbation in this study.Delta Med Col J. Jan 2018 6(1): 35-44